2005
DOI: 10.1124/jpet.105.093112
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Response to Angiotensin-Converting Enzyme Inhibition of Matrix Metalloproteinases 2 and 9 in Renal Glomerular Damage in Young Transgenic Rats with Renin-Dependent Hypertension

Abstract: Extracellular matrix expansion in the glomerular mesangium contributes to the development of glomerulosclerosis and chronic renal disease in arterial hypertension. Transforming growth factor-␤1 (TGF-␤1), matrix metalloproteinases (MMPs), and tissue inhibitors of MMPs (TIMPs) are involved in this process. Conflicting data are reported on the effects of angiotensin II (Ang II) and the response to angiotensin-converting enzyme inhibition on MMPs and TIMPs in early stages of hypertensive glomerular damage. We ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 38 publications
(47 reference statements)
2
25
0
1
Order By: Relevance
“…Experimental studies showed increased expression of MMP-2, but not MMP-9 in glomeruli in hypertensive glomerulosclerosis [1,7]. In humans the role of MMP-2 was confirmed in pathogenesis of tubulointerstitial fibrosis in diabetic nephropathy [11].…”
Section: Introductionmentioning
confidence: 85%
“…Experimental studies showed increased expression of MMP-2, but not MMP-9 in glomeruli in hypertensive glomerulosclerosis [1,7]. In humans the role of MMP-2 was confirmed in pathogenesis of tubulointerstitial fibrosis in diabetic nephropathy [11].…”
Section: Introductionmentioning
confidence: 85%
“…The probes and primers used for the rat genes encoding the angiotensin-converting enzyme (ACE), angiotensinogen, renin, (P)RR, transforming growth factor-beta (TGF-b) and glyceraldehyde-3-phosphate dehydrogenase have been previously described. 12,13 …”
Section: Real-time Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…6 Homozygous TGR(mREN2)27 animals develop severe hypertension at an early age and were therefore studied at 8 weeks of age as reported. 11 Rats were kept under conditions of regular 12 h diurnal cycles using an automated light switching device and climate-controlled conditions at a room temperature of 22 1C. The rats were fed a normal pelleted diet containing 0.2% sodium chloride (NaCl) and had free access to food and water.…”
Section: Methods Animalsmentioning
confidence: 99%